Characterization and screening of lipolytic bacteria from Thai fermented fish - Rungsima Daroonpunt,; Naoto Tanaka,; Masataka Uchino,; Somboon Tanasupawat, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Nine bacterial strains were isolated from Thai fermented fish by the standard dilution technique using JCM no. 377 medium. The rod shaped isolate FN2-3 was identified as Virgibacillus dokdonensis while isolates FN2-3 and FN6-6 as V. halodenitrificans, FN1-13 as Corynebacterium variabile, FN1-10 as Oceanobacillus iheyensis and FN3-7 was Bacillus amyloliquefaciens subsp. plantarum. The coccal isolates, FN6-1 and FN6-7 were Staphylococcus saprophyticus subsp. bovis and FN6-8 was S. saprophyticus subsp. saprophyticus, based on their phenotypic characteristics and 16S rRNA gene sequence analyses at a 99.63-100% sequence similarity. Their lipase activity in complex medium (CM), CM medium with 1% (v/v) Tween 20 or CM medium with 1% (v/v) Tween 80 ranged from 1.12 ± 0.03-3.77 ± 0.04 unit/mL, with the highest lipase activity found with V. dokdonensis FN1-8 cultivated with CM with 1% (v/v) Tween 80.